2013
DOI: 10.1371/journal.pgen.1003978
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Crossover Control by Concerted Action of Rad51-Dmc1 in Homolog Template Bias and Robust Homeostatic Regulation

Abstract: During meiosis, repair of programmed DNA double-strand breaks (DSBs) by recombination promotes pairing of homologous chromosomes and their connection by crossovers. Two DNA strand-exchange proteins, Rad51 and Dmc1, are required for meiotic recombination in many organisms. Studies in budding yeast imply that Rad51 acts to regulate Dmc1's strand exchange activity, while its own exchange activity is inhibited. However, in a dmc1 mutant, elimination of inhibitory factor, Hed1, activates Rad51's strand exchange act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
193
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(221 citation statements)
references
References 104 publications
(213 reference statements)
25
193
0
Order By: Relevance
“…VDE-initiated recombinants formed at high frequencies at both HIS4 and URA3, and NCOs exceeded COs by approximately twofold at HIS4 and threefold at URA3 ( Figure 2C). These values are within the range observed in genetic studies of Spo11-induced gene conversion in budding yeast (Fogel et al, 1979), but differ from the average of near-parity between NCOs and COs observed in molecular assays (Lao et al, 2013;Martini et al, 2006). This is Figure 2C from HIS4 insert-containing mutants lacking MutLg (mlh3), structure-selective nucleases (mms4-md yen1 slx1) or both resolvase activities (mlh3 mms4-md yen1 slx1).…”
Section: Resultssupporting
confidence: 57%
“…VDE-initiated recombinants formed at high frequencies at both HIS4 and URA3, and NCOs exceeded COs by approximately twofold at HIS4 and threefold at URA3 ( Figure 2C). These values are within the range observed in genetic studies of Spo11-induced gene conversion in budding yeast (Fogel et al, 1979), but differ from the average of near-parity between NCOs and COs observed in molecular assays (Lao et al, 2013;Martini et al, 2006). This is Figure 2C from HIS4 insert-containing mutants lacking MutLg (mlh3), structure-selective nucleases (mms4-md yen1 slx1) or both resolvase activities (mlh3 mms4-md yen1 slx1).…”
Section: Resultssupporting
confidence: 57%
“…Therefore, although the checkpoint clamp and Rad51 were recruited to single-stranded DSB ends independently of one another (Shinohara et al, 2003a), the two components function concurrently at the same sites to promote the progression of recombination intermediates during meiosis. In the absence of Rad51, intersister joint molecules were increased and interhomolog joint molecules decreased to a similar extent, suggesting a simple redistribution of joint molecule intermediates from homolog to sister (Hong et al, 2013;Lao et al, 2013;Schwacha and Kleckner, 1997). Taken together, these findings delineate a crucial role for Rad51-Dmc1 cooperation in interhomolog bias for meiotic recombination.…”
Section: Dna Damage Response Proteins Versus Rad51-dmc1 In Interhomolmentioning
confidence: 73%
“…However, this mechanism is unlikely because, unlike clamp-defective mutants, both rad51 and dmc1 mutants are proficient in Zip3-focus formation ( Fig. 5; Lao et al, 2013). These findings led us to the hypothesis that the 9-1-1 clamp, in addition to its role in homolog bias, is necessary for the efficient recruitment and/or stabilization of ZMM proteins along the developing synaptonemal complex.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has provided evidence that the essential role of Rad51 in meiosis is to enhance the recombinase activity of Dmc1 (10). These results thus reveal distinct functions of Rad51 and Dmc1 in meiotic HR (11)(12)(13). In mice, a homozygous deletion of Rad51 causes embryonic lethality.…”
Section: Homologous Recombination (Hr)mentioning
confidence: 94%